A83 CHROMOFUNGIN DECREASES INTESTINAL INFLAMMATION AND REGULATES DENDRITIC CELLS MARKERS - Kapoor, K (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Ulcerative colitis (UC) is characterized by altered levels of chromogranin-A (CHGA) and a dysregulation of dendritic cells (DCs). CHGA, a prohormone protein, can be cleaved into several bioactive peptides including chromofungin (CHR: CHGA(47-66)) encoded by CHGA Exon-IV. Previously, we demonstrated that CHR is reduced in active UC patients and protects against intestinal inflammation through modulation of the macrophages plasticity. Thus, we hypothesized that CHR regulates other antigen presenting cells functions like DCs during the progression of colitis. AIMS: We aimed to investigate the association between CHR and DCs in patients with active UC, and underlay the effect of CHR treatment on DCs functions in dextran sulfate sodium (DSS)-induced colitis. METHODS: mRNA levels of CHR (CHGA Exon-IV) and its association with DCs markers (interleukin (IL)-23, IL-12p40, CD86, CD11C, CRR7, CD74, IL-12A) were quantified in colonic biopsies of patients with active UC and healthy individuals. Colitis was induced in C57BL/6 mice (7–8 weeks) by 5% DSS (wt./vol.) for 5 days. Intra-rectal administration of CHR (2.5 mg/kg/day) started one-day before induction of colitis and lasted for 6 days. Disease activity index (DAI), macroscopic and microscopic scores were assessed. Colonic levels of interleukin (IL)-23, IL-12p40, cluster of differentiation (CD) 86, CD11C, C-C chemokine receptor (CCR)7, CD74 and IL-12A were determined using ELISA and/or RT-qPCR. In-vitro, splenic CD11c(+) cells were isolated from naïve and colitic mice, cultured overnight in the presence or absence of CHR (10(–6) M) and CD40, CD80, and CD86 markers were quantified using flow cytometry. RESULTS: In patients with active UC, CHR level is reduced and showed a negative relationship with DCs markers; IL23 (r= -0.3725), IL12p40 (r= -0.3706), CD11C (r= - 0.4647), CRR7 (r= -0.3709), IL12A (r = -0.4253), CD86 (r= -0.6765), and CD74 (r= -0.3647). In-vivo, CHR treatment reduced the severity of the colitis and is associated with a significant decrease in colonic levels of IL-23, IL-12p40, and CD86, and without significant changes in the levels of CD11c, CCR7, CD74, and IL-12A. In-vitro, CHR treatment reduced CD40 and CD80 expression in splenic CD11c(+)cells isolated from colitic mice when compared with PBS-treated group. No differences were detected in the expression of CD86. CONCLUSIONS: CHR regulates the development of colitis, and modulates CD11c(+) cells markers of immune activation. Further studies are warranted to understand the possible effects of CHR on the crosstalk between CD11c(+) cells and T-cells. These findings provide the foundation of future potential therapeutic strategies in UC. FUNDING AGENCIES: Mindel and Tom Olenick Scholarship in Gastroenterology